Bryophyte species diversity of forest ecosystems in Slovenia (intensive monitoring programme) - Kutnar, Lado (Zbornik gozdarstva in lesarstva, 2008)
As part of the Intensive Monitoring Programme (IM) of Forest Ecosystems in Slovenia, the bryophyte flora and vegetation have been studied on 11 IM plots and 64 vegetation sub-plots (10*10 m). On the IM plots, high species diversityof bryophytes has been assessed. The total number of bryophytes was 109; among them 82 species belonging to the mosses (Bryophyta) and 27 species to the liverworts (Marchantiophyta). The mean number per plot was 27 species, ranging from 13 species on the Brdo plot to 36 species on the Borovec and Draga plots. The most common moss species are Hypnum cupressiforme, Ctenidium molluscum, Tortella tortuosa, Brachythecium velutinum, Isothecium alopecuroides, Dicranum scoparium, Polytrichum formosum, Fissidens taxifolius,F. dubius (Bryophyta); and liverworts are Radula complanata, Chiloscyphus profundus, Plagiochila porelloides and Metzgeria furcata (Marchantiophyta). Regarding the substrate preference, the opportunistic species that inhabit very different substrates are prevalent; and the second main group are bryophytes inhabiting wood material (epiphyte, epixylic species). Using multivariate techniques (cluster analysis, DCA), the bryophytes have proved to be valuable indicator of site conditions (bedrock, surface rockiness, soil type, micro- and regional climate, vegetation) and forest stand conditions (dominant tree species, dead wood).
Keywords: gozdovi; mahovi; Slovenia; Slovenija